JBuilder essentials - Jensen, Cary (Osborne McGraw-Hill, 1998)
Inside you'll learn to leverage JBuilder's AppBrowser, design effective user interfaces, build Java-based database applications, debug and deploy Java applications and applets, and construct JavaBeans. In addition, JBuilder Essentials includes a comprehensive appendix on Java as well as complete coverage of JBuilder. And with a trial version of the JBuilder Professional Edition software on the CD-ROM, JBuilder Essentials contains everything you need to build sophisticated Java Applications and Applets today.